Research on Dual-Carrier Pulse-Train-Controlled Buck Converter - Ming Qin; Shiwei Li (Journal of Control Science and Engineering)
In order to solve the low-frequency oscillation of pulse-train- (PT-) controlled switching converter operating in a continuous conduction mode (CCM), a dual-carrier pulse-train (DCPT) control technique is proposed in this paper. With the CCM buck converter as an example, the operational principle, pulse control law, and output voltage ripple of the DCPT-controlled converter are studied. The experimental results are provided to verify the theoretical analysis and simulation results. Compared with the PT-controlled converter, the DCPT-controlled CCM buck converter enjoys much better operating characteristics and smaller output voltage ripple.